Increased incidence of Graves’ disease during the COVID-19 pandemic in children and adolescents in the United States - Pollack-Schreiber, Naama; Fishbein, Joanna S.; Nwosu, Benjamin Udoka; Salemi, Parissa (Frontiers in Endocrinology, 2024)
Reports in adults indicate that Severe Acute Respiratory Syndrome Corona Virus-2 (SARS-CoV-2) infection and vaccination trigger the expression of autoimmune disease such as Graves' disease, but the incidence of new onset Graves' disease and its temporal relationship to the peaks of COVID-19 cases in children are unclear.Methods: This is a retrospective study of children and adolescents with new-onset Graves' disease diagnosed between September 2017 to August 2022, N=156, mean age of 12.5±4 year (y), with a range of 2.9-17.9y. There were 119 female (76.3%) and 37 male (23.7%) subjects.Subjects were categorized into 2 groups: pre-COVID-19 era Graves' disease (n=63, age 12.5±3.3y), and COVID-19 era Graves' disease (n=93, age 12.4±4.4y). We calculated incidence rate based on new cases of Graves' disease and total number of new patient referrals to our endocrine clinic. We first compared the demographic, clinical and biochemical data between the above 2 groups; and also, between subjects with either a history of or vaccination (n=17) to a control group (n=63).The incidence of Graves' disease was significantly higher during the pandemic: pre-COVID-19 versus the COVID-19 era, n=55, 0.56% vs n=93, 0.9%, p=0.005, after accounting for the total number of annual new patient referrals during the study period. The rise in the cases of Graves' disease followed the spikes in the number of cases of COVID-19 in NY. There was also a statistically significant difference in the race distribution between the pre-COVID-19 and the COVID-19 era (p=0.026).: The incidence of Graves' disease increased significantly in children living in New York during the COVID-19 pandemic. The temporal relationship between the peaks of COVID-19 cases and the increased cases of new onset Graves' disease suggest possible autoimmune triggering by SARS-CoV-2.